Inclusive approaches to agribusiness: research at the cutting edge - International Center for Tropical Agriculture (2015)
Upstream academic research and downstream development practice are often divided - even when they share similar goals for empowering the rural poor. International agricultural research, through the CGIAR, has attempted to bridge this gap by combining research, capacity strengthening and development. An example is the Learning Alliance approach, applied by CIAT and CRS in thirty-five countries globally.